Translating proof-of-concept for platelet slip into improved antithrombotic therapeutic regimens - Scott J. Denardo; Pavlos P. Vlachos; Brett A. Meyers; Reza Babakhani-Galangashi; Lin Wang; Zejin Gao; James E. Tcheng (Platelets)
Platelets are central to thrombosis. Research at the intersection of biological and physical sciences provides proof-of-concept for shear rate-dependent platelet slip at vascular stenosis and near device surfaces. Platelet slip extends the observed biological “slip-bonds” to the boundary of functional gliding without contact. As a result, there is diminished engagement of the coagulation cascade by platelets at these surfaces. Comprehending platelet slip would more precisely direct antithrombotic regimens for different shear environments, including for percutaneous coronary intervention (PCI). In this brief report we promote translation of the proof-of-concept for platelet slip into improved antithrombotic regimens by: (1) reviewing new supporting basic biological science and clinical research for platelet slip; (2) hypothesizing the principal variables that affect platelet slip; (3) applying the consequent construct model in support of-and in some cases to challenge-relevant contemporary guidelines and their foundations (including for urgent, higher-risk PCI); and (4) suggesting future research pathways (both basic and clinical). Should future research demonstrate, explain and control platelet slip, then a paradigm shift for choosing and recommending antithrombotic regimens based on predicted shear rate should follow. Improved clinical outcomes with decreased complications accompanying this paradigm shift for higher-risk PCI would also result in substantive cost savings.